Alexis Wound Retractor for Radical Cystectomy: A Safe and Effective Method for Retraction. (9th December 2018) - Sidhu, Ajaydeep S.; Marten, Eric; Bodoukhin, Nikita; Wayne, George; Nagoda, Elizabeth; Bhandari, Akshay; Nieder, Alan M.
Abstract : Surgical site infection rates remain a common postoperative problem that continues to affect patients undergoing urologic surgery. Our study seeks to evaluate the difference in surgical site infection rates in patients undergoing open radical cystectomy when comparing the Bookwalter vs. the Alexis wound retractors. After institutional review board approval, we performed a retrospective chart review from February 2010 through August 2017 of patients undergoing open radical cystectomy with urinary diversion for bladder cancer. We then stratified the groups according to whether or not the surgery was performed with the Alexis or standard Bookwalter retractor. Baseline characteristics and operative outcomes were then compared between the two groups, with the main measure being incidence of surgical site infection as defined by the CDC. We evaluated those presenting with surgical site infections within or greater than 30 postoperatively. Of 237 patients who underwent radical cystectomy with either the Alexis or Bookwalter retractor, 168 patients were eligible to be included in our analysis. There was no statistical difference noted regarding surgical site infections (SSIs) between the two groups; however, the trend was in favor of the Alexis (3%) vs. the Bookwalter (11%) at less than 30 days surgery. The Alexis wound retractor likely poses an advantage in reducing the incidence in surgical site infections in patients undergoing radical cystectomy; however, multicenter studies with larger sample sizes are suggested for further elucidation.